1998
DOI: 10.1136/jnnp.64.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in epilepsy: a case controlled study of adults receiving disability benefits

Abstract: Objective-To compare the prevalence of non-organic psychiatric disorders among disabled patients of normal intelligence with epilepsy with the prevalence of similar psychiatric disorders among age and sex matched disabled patients with other somatic diseases. Methods-A case-control study was carried out in Iceland among people receiving disability benefits using information available at the State Social Security Institute. There were 344 patients with epilepsy in Iceland 16 to 66 years of age (inclusive) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
27
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 5 publications
6
27
0
5
Order By: Relevance
“…For example, community-based studies of epileptic patients with structured interviews have found prevalences of psychiatric comorbidities varying between 23.5% and 37.5%, always higher than in the general population (10-20%). In contrast, studies using ICD diagnoses and data from administrative registries have shown greater variation (16.8 to 60%) 5,15 . Larger prevalence was found in populations extracted from lists of individuals with some other associated disease, and therefore probably with a selection bias 5,15 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, community-based studies of epileptic patients with structured interviews have found prevalences of psychiatric comorbidities varying between 23.5% and 37.5%, always higher than in the general population (10-20%). In contrast, studies using ICD diagnoses and data from administrative registries have shown greater variation (16.8 to 60%) 5,15 . Larger prevalence was found in populations extracted from lists of individuals with some other associated disease, and therefore probably with a selection bias 5,15 .…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, studies using ICD diagnoses and data from administrative registries have shown greater variation (16.8 to 60%) 5,15 . Larger prevalence was found in populations extracted from lists of individuals with some other associated disease, and therefore probably with a selection bias 5,15 . The prevalence of psychiatric disorders seems to increase according with the severity of neurological disorders (Figure), in the following sequence: patients with chronic non-neurological diseases, patients with nonepileptic neurological diseases, patients with generalized epilepsies, patients with extratemporal focal epilepsies, patients with non-surgically treatable TLE, and finally, patients eligible for surgery 16 .…”
Section: Discussionmentioning
confidence: 85%
“…Dabei ist wichtig zu betonen, dass die körperliche Behinderung, die in der Gruppe der mental retardierten Patienten deutlich häufiger ist, keinen ausreichenden Grund liefert, um Unterschiede zu erklären, wie eine Case-control-Studie von behinderten normalintelligenten Menschen zeigte [29].…”
Section: Diskussionunclassified
“…Andererseits bieten die Wohnbereiche behinderter Menschen eine sehr gute Möglichkeit für Langzeitbeobachtungen [14,15,16]. Mit der Einschränkung durch die genannten methodischen und diagnostischen Probleme kommen die meisten Studien zu dem Schluss, dass wahnhafte (meist schizophreniforme) Psychosen häufiger bei Menschen mit Epilepsien und Behinderung auftreten als bei normalintelligenten Menschen [4,20,29].…”
Section: Diskussionunclassified
“…В одном из исследований [30] были установлены бо-лее высокие показатели ассоциации психотических со-стояний с эпилепсией по сравнению с заболеваниями со-матическими: частота возникновения психозов у мужчин в основной группе по сравнению с контрольной была в 3 раза выше (6,2 и 2,3% соответственно). По мнению G. Gudmundsson [31], такого рода данные не только сви-детельствуют о тесной связи эпилепсии и шизофрении, но и, возможно, объясняют виктимность пациентов с ши-зофренией (склонность к опрометчивым поступкам и провокационным действиям, которые приводят к не-счастным случаям, травмам).…”
unclassified